2022
DOI: 10.1002/adom.202102282
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Flexible Scintillation Screen Based on Manganese (II) Activated 2D Perovskite for Planar and Nonplanar High‐Resolution X‐Ray Imaging

Abstract: power. [1] X-ray detection technology, as a derivative of its own special properties, plays a key role in multiple applications, including medical radiography, safety surveillance, industrial flaw inspection, and scientific research. [2][3][4] Especially for the global pandemic of Corona Virus Disease 2019, X-ray radiograph and computed tomography scan were employed as rapid and accurate autodetection methods to reveal abnormal lung indications for disease diagnosis. [5] Modern X-ray detectors with the advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 48 publications
0
56
0
Order By: Relevance
“…X-rays are quite common in modern life and play an increasingly vital role in high-energy physics, nondestructive flaw detection, medical imaging, and other fields. At the hardware level of advanced medical imaging, the investigation of scintillators with balanced performance is a significant area. Experimental results and commercial applications have proven that metal halides, such as halide perovskites and some rare earth-doped materials, possess excellent scintillation properties. In 2018, Chen et al reported the scintillation properties of CsPbBr 3 perovskite nanocrystals (NCs) and demonstrated their applications in solution-processed high-resolution X-ray imaging . In the meantime, Im et al.…”
mentioning
confidence: 99%
“…X-rays are quite common in modern life and play an increasingly vital role in high-energy physics, nondestructive flaw detection, medical imaging, and other fields. At the hardware level of advanced medical imaging, the investigation of scintillators with balanced performance is a significant area. Experimental results and commercial applications have proven that metal halides, such as halide perovskites and some rare earth-doped materials, possess excellent scintillation properties. In 2018, Chen et al reported the scintillation properties of CsPbBr 3 perovskite nanocrystals (NCs) and demonstrated their applications in solution-processed high-resolution X-ray imaging . In the meantime, Im et al.…”
mentioning
confidence: 99%
“…Depending on the ligand field strength of the local host environment, d-d electron transition from transition metal ions, in particular, ions such as Mn 2+ , can provide broadband and tunable visible photoemission upon ultraviolet (UV) excitation, 33 offering a great opportunity for generating radioluminescence in inorganic optical materials for novel scintillators. Mn 2+ -activated scintillators with efficient radioluminescence are rarely reported, 5,23,[34][35][36][37] and there is no report on Mn 2+ -activated novel glass scintillators to our best knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Doping of transition metal Mn 2+ ions into perovskite (Mn 2+ ‐doped perovskite) NCs with PL QYs of ∼ 60% were first reported by Son's group 8 and Klimov's group 9 in 2016. The Mn 2+ ‐doped CsPbCl 3 NCs can produce a bright orange‐red Mn 2+ emission with a large Stokes shift which improves the stability of the host NCs while lowering toxicity 8–20 ; thus received wide research attention recently for exploring their various potential applications, typically, as phosphor materials applied in white LEDs, and as scintillators applied in fast neutron and/or X‐ray imaging 12,17,19 …”
Section: Introductionmentioning
confidence: 99%
“…7 Doping of transition metal Mn 2+ ions into perovskite (Mn 2+ -doped perovskite) NCs with PL QYs of ∼ 60% were first reported by Son's group 8 and Klimov's group 9 in 2016. The Mn 2+ -doped CsPbCl 3 NCs can produce a bright orange-red Mn 2+ emission with a large Stokes shift which improves the stability of the host NCs while lowering toxicity [8][9][10][11][12][13][14][15][16][17][18][19][20] ; thus received wide research attention recently for exploring their various potential applications, typically, as phosphor materials applied in white LEDs, and as scintillators applied in fast neutron and/or X-ray imaging. 12,17,19 For CsPbCl 3 NCs, the deep-level chloride vacancy (V Cl )type defects are in the middle levels within the band gap, which capture the electrons or holes to cause a nonradiative recombination, reducing the radiative recombination of carriers and weakening their optical quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation